Moringa extract enhances the fermentative, textural, and bioactive properties of yogurt. (March 2019) - Zhang, Ting; Jeong, Chang Hee; Cheng, Wei Nee; Bae, Hyojin; Seo, Han Geuk; Petriello, Michael C.; Han, Sung Gu
Abstract: Yogurt is a fermented dairy food produced by lactic acid bacteria (LAB). Moringa oleifera is known for its bioactive properties. The aim of this study was to evaluate the effects of moringa on the fermentation, quality characteristics, and bioactive properties of yogurt. Yogurt was supplemented with 0–0.2% moringa extract (ME; hot water extract, 100 °C, 30 min) and fermented using mixed starter cultures ( Streptococcus thermophilus, Lactobacillus acidophilus, and Bifidobacterium longum ). Addition of ME to yogurt significantly accelerated the rate of fermentation by promoting growth of LAB. ME reduced syneresis up to 21% and enhanced the water-holding capacity by 17%. The viscosity of 0.2% ME yogurt was approximately 5-fold higher than control yogurt and radical-scavenging activity of ME yogurt increased up to 40% in a dose-dependent manner during the 21 days of cold storage. Sensory testing showed that the addition of 0.05% ME to yogurt did not negatively influence the overall acceptability of the product, compared to the control. The addition of ME to yogurt decreased the oxidative stress and increased the expression of antioxidant proteins in human colon cells. Thus, ME-fermented yogurt maintains the sensory acceptability and exerts positive health benefits because of increased LAB proliferation and enhanced antioxidant properties. Highlights: Addition of moringa extract (ME) to yogurt accelerated fermentation rate. ME reduced syneresis and enhanced the water-holding capacity of yogurt. Viscosity and radical-scavenging activity increased in ME yogurt over 21 days. ME increased the expression of antioxidant proteins in human intestinal cells. ME yogurt maintains sensory acceptability and possesses antioxidant effects.